A new tuning method based on quantitative compensation for uniform and non-uniform travelling-wave accelerating structures - Yu Yang; Bo Wang; Jinghe Yang; Aijun Cui; Yuepeng Lv; Cheng Qin; Yihuai Xiang; Lifeng Zhang; Zhibin Zhu (Results in Physics)
In this paper, a new tuning method based on quantitative compensation for both uniform and non-uniform structures is proposed after analyzing the relationship between field distribution and RF parameters of each cavity based on the equivalent circuit model. Using field distributions measured when RF power is fed respectively into input and output ports, the frequency deviation of each cavity and both input and output coupling coefficients of the structure can be calculated quantitatively. The reflection caused by coupling coefficient deviation can be eliminated by detuning coupler cavity and the adjacent cavity quantitatively. And the frequency deviation, which is usually tuned by the tuning hole on the cavity, can be also compensated quantitatively by detuning the adjacent cavities especially when it’s not convenient or too large to be tuned by the tuning hole. A S-band non-uniform travelling wave accelerating structure has been tuned successfully with this method. The field distribution is tuned to be close to the design, the VSWR at the operating frequency is minimized to 1.0056 and these results verify the effectiveness of this method